Taurine Is a Major Carbon and Energy Source for Marine Prokaryotes in the North Atlantic Ocean off the Iberian Peninsula - Elisabeth L. Clifford (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Marta M. Varela (Instituto Español de Oceanografía (IEO), Centro Oceanográfico de A Coruña); Daniele De Corte (Research and Development Center for Marine Biosciences, Japan Agency for Marine-Earth Science and Technology (JAMSTEC)); Antonio Bode (Instituto Español de Oceanografía (IEO), Centro Oceanográfico de A Coruña); Victor Ortiz (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Gerhard J. Herndl (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Eva Sintes (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna) (Microbial Ecology, 2019)
The abstract is available here: https://uscholar.univie.ac.at/o:1078857 The abstract is available here: https://uscholar.univie.ac.at/o:1078857